Do credit cards trigger conspicuous consumption? Evidence from Turkish households - ACET DÖNMEZ, GİZEM; GÜNEŞ, HURŞİT (My University, 2022)
Consumption decisions of individuals sometimes contradict with the neoclassical assumption of rationality. Veblen’s concept of conspicuous consumption is often regarded as a specific case of this irrationality because expenditures on conspicuous items are seen as wasteful. Another form of irrational behaviour takes place when consumers pay their purchases with a credit card. For instance, instalment payments offered by credit cards shift consumers’ attention from the total cost to the amount of monthly payment, and thereby lead consumers to spend unreasonably more. This study aims to examine the connection between these two concepts -conspicuous consumption and credit card usage- in Turkey. Household Budget Survey 2019 of TurkStat has been utilized for this purpose. Following the literature, spendings on products related to appearance (i.e., clothing, footwear, and accessories) -above a particular threshold- have been assumed as conspicuous consumption expenditures. The results of the weighted ordinary least squares estimation have demonstrated that credit card user households spend significantly more on conspicuous items compared to households who do not use any credit card. This connection prevails even after controlling for income level of the household as well as some demographic characteristics, and the findings are robust to the choice of threshold.
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Social Sciences and Humanities; Economics; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities